Las voces de la diversidad y los silencios de lo común: las identidades a debate - Sánchez Capdequi, Celso (Política y Sociedad, 2010)
This paper sets out to explain the relation between the sociological theory and the image of identity in several environments of our society, especially, in education. Sociological discussion focuses on the problem of diversity and promotes the distancing between lifestyles, cultures and religions. These social groups are the new subjects of the global society. This fact influences selfunderstanding of the social groups and on the patterns of socialization and education.